Bacteriological and Physicochemical Quality Assessment of Drinking Water Sources in Ilorin, Nigeria - Tomilayo, R. B.; Azeez, R. T.; Azeez, T.; Okwechime, P. O. (Al-Hikmah Journal of Pure and Applied Sciences (AJPAS), 2026)
Guarantee on safe drinking water is indispensable for public health; quality varying across sources in Nigeria. This work assessed sachet (SW), bottled (BW), and borehole (BH) drinking water from Tanke, Ilorin, exploring physicochemical profiling, culture-based microbiology (heterotrophic, fecal coliform counts), biochemical identification, and antimicrobial susceptibility testing measure against WHO guidelines. The results on physicochemical parameters revealed acceptable pH (6.567.30), chloride, hardness, sulphate and nitrate. Borehole samples had electrical conductivity (1163–1175 µS/cm) exceeded guidelines values ≤1000 µS/cm), total dissolved solids at borderline-high in BH (500 mg/L), a sachet sample (SW2: 743.5 mg/L) exceeding the ≤500 mg/L limit. Critically, lead concentrations in borehole were extremely elevated (2.032–2.070 mg/L; guideline ≤0.01 mg/L), severe chemical risk implicated. Heterotrophic bacterial counts (cfu/mL), were low in all sources: SW ranged 20–40, BW ranged 0–20, and BH ranged 0–40. Biochemical characterization recovered opportunistic Gram-negative rods from borehole water (Alcaligenes faecalis and Proteus vulgaris), environmental/handling-associated taxa from sachet water (Bacillus subtilis, Serratia marcescens, Staphylococcus aureus and Streptomyces sp.), and commensals from bottled water (Staphylococcus sp., Micrococcus luteus and Streptococcus sp.). Antimicrobial testing showed widespread resistance among several isolates, including Proteus vulgaris and Staphylococcus aureus, implying environmental reservoirs of resistance. Overall, packaged waters were microbiologically acceptable, having no coliforms and very low total heterotrophic bacterial counts, but, physiochemically non-compliant (SW2 TDS). Borehole water however, presented significant chemical hazards (lead, EC) and opportunistic organisms. Findings therefore, support urgent borehole remediation, tighter sachet production controls, and continued bottled water verification, integrating antimicrobial resistance surveillance into local water safety planning.